IMPROVEMENT IN NUMBER AND QUALITY PRODUCTION OF SEED GROUPER FISH BY NATURAL FEED ENRICHMENT - Suko Ismi; Yasmina Nirmala Asih (Jurnal Ilmu dan Teknologi Kelautan Tropis, 2014)
ABSTRACT Some researches on grouper seed production have been conducted and their results have been adopted by the farmer. Currently, grouper seeds for mariculture purposes can be provided from hatchery. However, seed abnormality is still the major problem in the hatchery.  Therefore, an improvement for survival rate and quality of grouper seed production is very important. The aim of this study was to improve the production and reduce the abnormalities on grouper seed stock through enrichment of larvae feed (rotifer and artemia) with DHA and EPA, Vitamin and Calcium. The larvae of humpback grouper (Cromileptes altivelis) were reared with and without enrichment. The experiment were held in concrete tank with volume of 10 m3 filled with sea water 7-8 m3. Grouper eggs were stocked at a density of 10 eggs/l, larval were reared until the juvenile age of 45 days.  Treatment were repeated three times. The data was analysed with descriptive statistic. The results showed that humpback grouper larvae reared with enriched rotifers and artemia produced better survival rate (26.81%), lower seed abnormality (26.10%), and better percentage of bigger size of seeds with grade A (20.3 %), B (39.2%), and C (40.5%).  Meanwhile, treatment without feed enrichment produced lower survival rate (17.57%), higher abnormality (40.20%), and lower percentage of big size of seeds with grade A (9.7%), B (26.0%), and C (64.3%). Keywords: groupers, quality, enrichment, improvement, production